2018
DOI: 10.1186/s12889-018-5784-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-reported eating speed and metabolic syndrome in a Beijing adult population: a cross-sectional study

Abstract: BackgroundResearch on the relationship between metabolic syndrome (MetS), its components and eating speed is limited in China. The present study aimed to clarify the association between MetS, its components and eating speed in a Beijing adult population.MethodsThis cross-sectional study included 7972 adults who were 18–65 years old and who received health check-ups at the Beijing Physical Examination Center in 2016. Logistic regression was conducted to explore the associations between MetS, its components and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 39 publications
5
75
1
Order By: Relevance
“…Eating fast is known to be associated with overweight and obesity [9][10][11], insulin resistance [16], metabolic syndrome [10,17] and T2DM [16,18]. Eating fast is also reported to be associated with a risk factor for CVD [31], which is associated with NAFLD [4,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating fast is known to be associated with overweight and obesity [9][10][11], insulin resistance [16], metabolic syndrome [10,17] and T2DM [16,18]. Eating fast is also reported to be associated with a risk factor for CVD [31], which is associated with NAFLD [4,32].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, eating speed is reported to be associated with insulin resistance [16]. Moreover, it has been shown that eating fast is associated with metabolic syndrome [10,17] and T2DM [16,18]. Furthermore, several studies have also revealed that eating fast is associated with NAFLD in the general population [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly in humans, a positive association was obtained between eating speed and overweight (Lee et al, ; Tanihara et al, ) and eating speed and metabolic syndrome among other health problems (Nohara et al, ; Tajima et al, ; Tao et al, ; Zhu, Haruyama, Muto, & Yamazaki, ). Fast eaters tend to be more obese, have higher blood pressure and be more susceptible to metabolic diseases than slow eaters.…”
Section: Discussionmentioning
confidence: 99%
“…Fast eaters tend to be more obese, have higher blood pressure and be more susceptible to metabolic diseases than slow eaters. The estimated odds ratio between normal and fast‐eating individuals for overweight in the Japanese adult population was 1.9 (Lee et al, ) and between slow and fast‐eating individuals for metabolic syndrome in the Chinese adult population 2.3 (Tao et al, ). Given the similar metabolic system in pigs and humans, pigs can be used as an animal model for further investigation of the mechanism behind the unfavourable association between eating (or feeding) speed and accumulation of body fat.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic literature review, fast eating speed is associated with increase of body mass index (BMI) and obesity [ 15 ]. Among Chinese adults aged between 18 and 65 years, fast eating is significantly associated with high incidence of MetS and is related to elevated blood pressure and abdominal obesity among the components of MetS [ 16 ]. A study on Korean hospital nurses’ dietary habits reported that time allocated for a meal while on duty was 16–28 min on average; this differed depending on work shift.…”
Section: Introductionmentioning
confidence: 99%